Study of Career Education for Women: Development of Global Human Resources - Mayumi Hori (International Journal for Applied Information Management, 2021)
We are facing a rapid population decline caused by a declining birth rate. To keep our nation growing, we need to develop the capabilities of the next generation of diverse global human resources that provide us with a higher quality of life. To create innovation, it is necessary to develop global human resources who have advanced technical skills and combined capabilities such as thinking and management, as well as to create new added value. Unfortunately, women's working conditions are not the same as men's. Even though female labor force participation is increasing. the higher the level and level of education of women, there are still women who experience sex discrimination in the workplace where the traditional concept of gender roles still persists. The goal of Global Human Resource Development is to overcome the "inward tendencies" of students and to foster human resources who can positively respond to challenges and succeed in the global field, as a basis for increasing global competitiveness and strengthening brotherhood among nations. onment environment and maintain their career.